Regulating Personal Data : Data Models and Digital Services Trade - Ferracane, Martina Francesca (World Bank, Washington, DC, 2021)
While regulations on personal data diverge widely between countries, it is nonetheless possible to identify three main models based on their distinctive features: one model based on open transfers and processing of data, a second model based on conditional transfers and processing, and third a model based on limited transfers and processing. These three data models have become a reference for many other countries when defining their rules on the cross-border transfer and domestic processing of personal data. The study reviews their main characteristics and systematically identifies for 116 countries worldwide to which model they adhere for the two components of data regulation (i.e. cross-border transfers and domestic processing of data). In a second step, using gravity analysis, the study estimates whether countries sharing the same data model exhibit higher or lower digital services trade compared to countries with different regulatory data models. The results show that sharing the open data model for cross-border data transfers is positively associated with trade in digital services, while sharing the conditional model for domestic data processing is also positively correlated with trade in digital services. Country-pairs sharing the limited model, instead, exhibit a double whammy: they show negative trade correlations throughout the two components of data regulation. Robustness checks control for restrictions in digital services, the quality of digital infrastructure, as well as for the use of alternative data sources.